Tourettism in a 73 year-old man after coronary artery by-pass surgery - (:unkn) unknown (My University, 2009)
Koroner arter bypass greft cerrahisinden (KABGC) sekiz ay sonra motor ve vokal tikleri gelişen bir olguyu sunuyoruz. Burnunu karıştırma ve sümkürme gibi birkaç motor tik ve bağırma şeklinde bir vokal tik görülen hasta, öncül duyusal uyaranlar da tanımladı. Bu tiklerin ilk kez KABGC'den sonra ortaya çıkmış olması olgumuzun önemli özelliğidir. Manyetik rezonans görüntüleme bilateral bazal gangliyonlarda iskemik alanlar ve tek foton emisyon bilgisayarlı tomografi incelemesi sağ kaudat nukleusta ve bilateral frontotemporoparietal kortekste hipoperfüzyon göstermiş olup, bu alanlar tik patogenezi ile ilişkili beyin bölgeleridir. KAGBC öncesi kraniyal görüntülemelerin olmaması nedeniyle kesin bir çıkarımda bulunmak güç olmakla birlikte, tiklerin KABGC sırasındaki perfüzyon anomalisinin sonucunda ortaya çıktığı öne sürülebilir.

We present a patient who developed motor and vocal tics eight moths after a coronary artery bypass graft surgery (CABGS). The patient demonstrated a few motor tics like picking, blowing his nose and a vocal tic in the form of shouting. He also described premonitory sensory urges. Appearance of these tics for the first time ever after the CABGS in a 73 year-old male patient is the significance of our case. The patient had ischemic regions in the bilateral basal ganglia in the magnetic resonance imaging (MRI) and his single photon emission tomography (SPECT) examination revealed hypoperfusion in right caudate nucleus and bilateral frontotemporoparietal cortex which are the brain regions associated with tic pathogenesis. Although reaching a definitive conclusion is difficult since we do not have preoperative cranial imaging, we suggest that tics might have appeared as a result of perfusion abnormality he had incurred during the CABGS.
Koroner arter bypass cerrahisinden sonra 73 yaşındaki bir erkek hastada tourettizm
Keywords: Genel ve Dahili Tıp